Turbine inlet temperature measurement for control and diagnosis in combined cycle gas turbine - Parmar, J. (Cranfield University, 2002)
The author was responsible for the Guarantee verification, testing and eventually Acceptance of all of National Power's Combined Cycle Gas Turbines for its commercial operation. It was discovered during the early Acceptance Testing of these power stations that the Original Equipment Manufacturers (OEMs) used empirical and indirect ~-~; methods to derive the gas turbine inlet temperature. This had direct impact on the life of the gas turbine components and revenue earned in terms of increase in maintenance costs and loss in generating power. It became absolutely imperative that alternative methods should be quickly deployed on National Power's gas turbines to substantiate or otherwise the already used indirect methods of running the gas turbines. A completely novel method of using ceramic thermocouples probes and embedded ceramics onto blades to monitor elevated gas temperatures from the early trials on large coal fired boilers to specially made burner rigs and the Spey gas turbine are discussed. A patent for the ceramic temperature probe was filed and approved. Finally, a non-intrusive infra-red thermal pyrometry was installed on two of National Power's CCGT power stations. The report includes technical aspects on emissivity, radiation, risks, obstacles encountered, and the methodology used to install the pyrometry. Using the data collated from Deeside Power Station, where two pyrometers are currently installed, the results obtained from the engine simulation are validated. Once the model was validated and the data correlated with the actual data obtained, it can be concluded that the deployment of pyrometry can control the diagnostics and operational behaviour of the CCGT plant. The efficiency of the gas turbine was shown to increase by about 0:4% and the corresponding increase in power was 1.3%, which would make a substantial savings in the operating and maintenance costs to National Power. This was estimated to be in access of £25,OOO,OOOlannum.